Transformación de la práctica docente en sesiones de refuerzo de inglés mediante educación experiencial: un estudio de caso (2026)
The present study is conducted under a case study approach with the aim of reflecting on and transforming teaching practice in individual English reinforcement sessions through experiential education strategies. The research emerges from the need to understand how pedagogical decisions influence the participation and motivation of a second-grade student during the learning process, using attention as an observable pedagogical indicator to analyze teaching practice. This process is carried out from a reflective and contextualized perspective. This case study, developed in the context of home-based English reinforcement with an eightyear-old second-grade student, examines how teaching practice is transformed through the implementation of experiential education strategies across seven sessions conducted between August 26 and October 21, 2025. The research is structured in phases of diagnosis, planning, implementation, observation, and reflection/adjustment of practice, in coherence with a process of inquiry and continuous improvement. Attention is assumed as an observable pedagogical indicator to interpret the relationship between teaching decisions, student participation, and tutoring conditions. Classroom records also revealed a decrease in the number of interventions required to reorient attention, from eight reminders in an initial session to four in a later session. The pedagogical proposal incorporated situated and motivating activities, such as vocabulary games, reading and comprehension activities on Raz-Kids, dialogue about the student’s interests, and travel simulation, which fostered student participation and supported teacher reflection at the end of each session. It is concluded that experiential education, when applied to reinforcement tutoring, provides a viable pathway for transforming teaching practice through explicit and assessable pedagogical decisions, articulating qualitative evidence and light quantitative data to support concrete changes.